Long-Range Ballistic Missile Defense in Europe. (U.S. Congressional Research., 2008)
Discusses issues surrounding U.S.-proposed long-range ballistic missile defense system, comprising radar and antiballistic missile installations, to be based in Europe. Explains international and Congressional reaction to proposal, and positions of Presidential candidates.